MOOC: RECONSTRUCTION OF HIGHER EDUCATION - Dendev Badarch; Natalia Tokareva; Marina Tsvetkova (Высшее образование в России)
The article presents the materials corresponding to the major directions of new forms of online training in the system of higher education. Materials are prepared on the basis of the researches conducted by the UNESCO IITE during 2010-2014 on topical problems and tendencies of using massive open online courses as new forms of distance education, and also contains the analysis of modern educational platforms transformation during the development of the Web 2.0 as thenew information and educational environments conforming to the requirements of forming global knowledge society. New ICT change the educational environment, forms global university communities, open higher education to all people for lifelong learning, provide an exchange and promote creation of new of knowledge, but also form the advanced instruments of educational activity.